2019
DOI: 10.1080/15290824.2018.1532571
|View full text |Cite
|
Sign up to set email alerts
|

Finding Your Balance

Abstract: Professional dance careers require years of intensive training. Stress experienced during training must be balanced with adequate recovery to prevent overtraining and burnout. Little is known, however, about how dancers achieve recovery-stress balance. This study examined dancers' recollection of stress and recovery during their vocational dance training to identify potential stressors and recovery behaviors in vocational dance training. Twelve current and ex-professional ballet (n=4) and contemporary dancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Positive personality (37 studies) describes dancers that are striving for self-actualization, self-assessment, self-efficacy, self-management, autonomy, self-development, flexibility, and versatility. Several studies suggested that these factors aid dancers to form a holistic identity or buffer stressors they encounter ( van Staden et al, 2009 ; Klockare et al, 2011 ; Mitchell et al, 2017 ; Blevins et al, 2020 ; de Las Heras Fernández et al, 2020 ). However, according to the included studies, these qualities are deemed in need of development, nurturing, and strengthening, not only in dance but in future dance research in general.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive personality (37 studies) describes dancers that are striving for self-actualization, self-assessment, self-efficacy, self-management, autonomy, self-development, flexibility, and versatility. Several studies suggested that these factors aid dancers to form a holistic identity or buffer stressors they encounter ( van Staden et al, 2009 ; Klockare et al, 2011 ; Mitchell et al, 2017 ; Blevins et al, 2020 ; de Las Heras Fernández et al, 2020 ). However, according to the included studies, these qualities are deemed in need of development, nurturing, and strengthening, not only in dance but in future dance research in general.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence relating to protective personal qualities revealed that buffering attributes, such as confidence, were presented as suggestions for further research rather than practically applied and explored ( Kveton-Bohnert, 2017 ; Blevins et al, 2020 ; Carattini, 2020 ; Kim et al, 2022 ). Therefore, protective personal qualities should be seen as useful suggestions and indications for further research, rather than established evidence in the dance context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Blevins et al 44 stated that little is known about dancers' management strategies of the recovery-stress balance to maintain and improve performance. Blevins et al 45 found in their study on ballet and contemporary dancers that "maladaptive behavioural responses (e.g., ignoring injury, pain, and fatigue) were related to negative training outcomes associated with overtraining and burnout." Dancers may have an inadequate understanding of the importance of recovery as part of their training program.…”
Section: Recovery-stress States Of Professional Ballet Dancers During...mentioning
confidence: 99%
“…Hill acknowledges the physical and mental stresses placed on the dancers and has been proactive in exploring means to support the dancers through the creation, performance and recovery from her productions. To avoid the incidence of overtraining and burnout that is common in the competitive world of contemporary dance (Blevins et al 2020), Hill incorporates remedial and supplemental training into typical company schedules. Hill identifies these processes as essential for the dancers to be able to fully commit to the work, achieve sufficient recovery to minimize injury risk and facilitate ongoing effort and engagement through the making and performance of the work.…”
Section: Co3mentioning
confidence: 99%